Carcass wrote:
The functions f and g are defined as f(x) = 2x – 3 and g(x) = x + \(\frac{3}{2}\). For what value of y is f(y) = g(y – 3) ?
(A) 1
(B) \(\frac{3}{2}\)
(C) 2
(D) 3
(E) 5
If f(x) = 2x – 3, then f(
y) = 2
y – 3
If g(x) = x + \(\frac{3}{2}\), then g(
y – 3) =
y – 3 + \(\frac{3}{2}\)
We want:
f(y) = g(y – 3)We can rewrite this equation as: 2
y – 3 =
y – 3 + \(\frac{3}{2}\)
Add 3 to both sides to get: 2y = y + \(\frac{3}{2}\)
Subtract y from both sides to get: y = \(\frac{3}{2}\)
Answer: B
Cheers,
Brent